PENGARUH KOMPENSASI, PENGEMBANGAN KARIR, DAN BUDAYA ORGANISASI, TERHADAP PRODUKTIVITAS PADA KARYAWAN BAGIAN OPERATIONAL DEPARTEMENT PT.PANCARAN DARAT TRANSPORT - Sarayar, Wulandari Angela Mericci; Saragih, Lisnatiawati (SWOT : Jurnal Ilmiah Ilmu Manajemen, 2022)
This study aims to analyze the effect of compensation, career development, and organizational culture on employee productivity in the operational department of PT. Pancaran Darat Transport. The population in this study were 92 operational employees of the PT. Pancaran Darat Transport. The sample used was 92 employees. The sampling method uses saturated sampling technique. Methods of data collection using survey methods, with the research instrument is a questionnaire. Data analysis method using Partial Least Square. This study proves that compensation has a positive and significant effect on employee productivity. Career development has a positive and significant effect on employee productivity. Organizational culture has a positive and significant effect on employee productivity.